MAKNA KAMISAN OLEH ANGGOTA PADA AKSI PENEGAKAN HAM - Tryan Nugraha (UNIVERSITAS PAKUAN, 2022)
Kamisan action in the city of Bandung is an act of upholding human rights from various cases of past gross human rights violations that have not been resolved until now. The Kamisan action also became an act of solidarity among its members to the families of victims of human rights violations in the past, although this Kamisan member in the city of Bandung is not a family of victims of past human rights violations. This research was conducted to find out the meaning, motives, backgrounds, and communication experiences of the Kamisan members in the city of Bandung. The research method used in this research is phenomenology with qualitative analysis techniques. Data collection techniques used in this study are in-depth interviews, observation, and documentation. Researchers conducted data analysis based on Snowball Sampling Models. From the results of this study, it is known that although the Kamisan members are not from the families of victims of past gross human rights violations, the members interpret the Bandung Kamisan actions as a form of upholding human rights as well as solidarity actions for the victims' families. The motives of the Kamisan members are the awareness of the members, the struggle to uphold justice, and educating the members as well as the general public, as well as their existence. From communication experience, it can be found that Kamisan actions are made into public spaces, as knowledge increases, and learning about organizations. The recommendation that can be given through this research is that Kamisan members in the city of Bandung should carry out further reviews related to education to the general public about the actions they take every week.